Expression of Concern to: Diet restriction inhibits apoptosis and HMGB1 oxidation and promotes inflammatory cell recruitment during acetaminophen hepatoxicity - Daniel James Antoine; Dominic P. Williams; Anja Kipar; Hugh Laverty; B. Kevin Park (BMC, 2020)
Abstract The Editors-in-Chief would like to alert readers that this article [1] is part of an investigation being conducted by the journal following the conclusions of an institutional enquiry at the University of Liverpool with respect to the quantitative mass spectrometry-generated results regarding acetylated and redox-modified HMGB1.